Social Responsibility and Hospitality: Strengthening Tourism on the Costa da Mata Atlântica/Brazil - Pozo, Hamilton; Silva, Thames Richard; Souza-Mossini, Fábio Emmerich; Durante, Denise; Guimarães, Luciana Maria (Archives of Business Research, 2023)
This study aims to expand the analysis of and initiatives in implementing social responsibility in hospitality and tourism. To this end, a theoretical scenario of the specific nature of social responsibility and hospitality was configured to understand what shapes organizations' decision-making factors regarding market principles. Social responsibility, often confused with philanthropy, has become of utmost importance for organizations given the present context of global climate change and the search for sustainability. Hospitality is a differentiating factor and competitive advantage for companies seeking to maintain a strong market position. The methodological approach adopted was a case study based on two data sources: a literature review and other empirical qualitative and quantitative studies. That resulted in a research tool applied to eight Costa da Mata Atlântica, Brazil tourism organizations. The results reveal beliefs and values that influence these organizations' increased involvement and interaction in tourism. The findings have implications primarily for strengthening tourism in the Costa da Mata Atlântica and supporting the development of a management framework for the organizations surveyed.